Magnetically active transition metal cation-substituted alumina. (16th December 2019) - Li, Changning; Ku, Nicholas; Liu, Yaohua; Pan, Jinbo; Chai, Binbo; Hu, Feng; Kornecki, Michael; Yan, Qimin; Brennan, Raymond; Ren, Shenqiang
Abstract: Alumina (Al2 O3 ) is one of the most widely used ceramic materials for innumerable applications, due to its unique combination of attractive physical and mechanical properties. These intrinsic properties are dictated by the numerous phases that Al2 O3 forms and its related phase transformations. Transition metal (TM) cation dopants (iron (Fe), cobalt (Co), nickel (Ni) and manganese (Mn)), even in sparse amounts, have been shown to significantly affect the phase transformation and microstructural evolution of Al2 O3 . Small concentrations of TM cation dopants have successfully been incorporated to synthesize magnetically active Al2 O3, while reducing the θ to α phase transformation temperature by 150 °C, and maintaining the outstanding mechanical properties. In addition, first-principle calculations based on density-functional theory with hybrid functional (HSE06) and the PBE+U methods have provided a mechanistic understanding of the formation energy and magnetism of the TM-doped α and θ phases of Al2 O3 . The results reveal a potential route for phase transition regulation and external magnetic field-induced texturing of Al2 O3 ceramics.